Modeling saccade reaction time in marmosets: the contribution of earlier visual response and variable inhibition - Amly, Wajd; Chen, Chih-Yang; Isa, Tadashi (Frontiers in Systems Neuroscience, 2024)
Marmosets are expected to serve as a valuable model for studying the primate visuomotor system due to their similar oculomotor behaviours to humans and macaques. Despite these similarities, differences exist; challenges in training marmosets on tasks requiring suppression of unwanted saccades, having consistently shorter, yet more variable saccade reaction times (SRT) compared to humans and macaques. This study investigates whether the short and variable SRT in marmosets is related to differences in visual signal transduction and variability in inhibitory control. We refine a computational SRT model based on (Coe et al., 2019), adjusting parameters to better capture the marmoset SRT distribution in a gap saccade task. Our findings indicate that visual information processing is faster in marmosets, and that saccadic inhibition is more variable compared to other species.